Energy and elemental composition (C, N, H) in growing megalopa of an edible crab Charybdis variegata (Fabricus) - Kumaresan, S; Soundarapandian, P; Karuppiah, S P; Kannupandi, T (Indian Journal of Fisheries, 2011)
The larval development of Charybdis variegata consists of five zoeal and one megalopa stages. The megalopa stage appears as a miniature adult or a preadult. Hence a radical change is expected functionally in the form of changes in biomass-dry weight, energy, elemental composition (C, N, H), respiration and excretion. In the laboratory, the dry weight of individual megalopa increased from 226.18 to 439.22 ug, carbon increased from 73.80 to 166.70 ug/ind, hydrogen and nitrogen content range was from 10.12 to 22.6 ug and 17.9 to 39.18ug respectively. C : N ratio in the 0 day was 4.0:1.0 and in 6th day it was 4.1:1.0. C : H ration in the 0 day was 7.2 : 1.0 and in 6th day it was 7.3 : 1.0.